2016
DOI: 10.1590/0103-8478cr20131515
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acids in the xylem sap of pear trees during dormancy

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…The release of buds from dormancy and the resumption of growth have been accredited to mechanisms regulating changes in metabolic activity and amino acids. 24 In addition, Wang and Faust 29 on apple found that arginine levels increased during March and April reaching the maximum at the end of April. From the onset of May, they decreased gradually until they reached a steady level at the end of July and beginning of August.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The release of buds from dormancy and the resumption of growth have been accredited to mechanisms regulating changes in metabolic activity and amino acids. 24 In addition, Wang and Faust 29 on apple found that arginine levels increased during March and April reaching the maximum at the end of April. From the onset of May, they decreased gradually until they reached a steady level at the end of July and beginning of August.…”
Section: Discussionmentioning
confidence: 98%
“…25 Moreover, Kuroi 47 indicated that N (including amino acids) was present at low levels in buds or roots during the dormant stage, and reached a maximum level just prior to bud break. In this connection, Marafon et al 29 reported that storage and remobilization are considered key processes for the effective use of nitrogen in temperate fruit trees. As dormancy begins, storage proteins are synthesized, coinciding with a reduction in the levels of free amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrus pyrifolia (Marafon et al, 2016(Marafon et al, , 1137, sin embargo, la mayoría de los trabajos se han realizado en condiciones controladas (Millard y Grelet, 2010, 1083.…”
Section: Introductionunclassified
“…: 207 -223 -210 -caída de las hojas y se movilizan en primavera (Bazot , 1024 Gilson et al, 2014, 117; Rennenberg et al, 2010, 276).Los estudios realizados sobre las reservas de N se han llevado a cabo en plantas herbáceas anuales (Valenzuela-Núñez et al, 2010, 76), mientras las investigaciones en especies leñosas son escasas, resaltando Populus spp. (Cooke y Weih, 2005, 20), Hevea brasilensis (Tian et al, 1998, 153), Swietenia macrophylla (Tian et al, 2003, 492), Picea sitchensis (Proe y Millard, 1994, 76),Prunus avium (Millard et al, 2006, 528), Quercus robur (Valenzuela-Núñez et al, 2011, 142) yPyrus pyrifolia (Marafon et al, 2016(Marafon et al, , 1137, sin embargo, la mayoría de los trabajos se han realizado en condiciones controladas (Millard y Grelet, 2010, 1083.Los estudios que abordan el almacenamiento de compuestos nitrogenados en el tallo (El Zein et al, 2011, 1391 y la movilización de nutrientes hacia los tejidos de nuevo crecimiento son escasos (Villar-Salvador et al, 2015, 819). En múltiples ocasiones los elementos nutritivos satisfacen la demanda de las plantas, ya sea por factores ambientales o por su disponibilidad en el medio ambiente (Millard y Grelet, 2010, 1091).…”
unclassified